Transformation Proposal for Tax Audit Policy in Indonesia: A Comparative Study on the Implementation of Tax Audit Policy in the Netherlands - Vishnu Juwono; Lucas Filberto Sardjono; Lambang Pujo Nagoro; Esi Sekar Rini; Dodik Siswantoro (Pusjar SKPP Lembaga Administrasi Negara, 2022)
A tax audit policy is intended to increase taxpayer compliance and trust towards tax authority. In Indonesia, the low level of trust carried out by tax audits observed from the taxpayer compliance level shows the shortcoming of implementing the tax audit system. Based on this phenomenon, this study is conducted to describe problems regarding the implementation of tax audit policy in Indonesia and provide recommendations for the Indonesian tax authority to transform tax audit policy practised by the tax audit system in the Netherlands. The Netherlands was selected as the research site, for this country is one of the OECD pioneers and has been part of AEoI. This study applied a qualitative approach. An in-depth interview was used to collect the data from competent parties in tax audits, both in Indonesia and the Netherlands. The findings showed that two factors caused the shortcoming of the tax audit system in Indonesia. First, the database was not maximal due to nonoptimal digitalisation and data integration. Second, the selection system for taxpayers to be audited was closed. Therefore, this study recommends that tax authorities in Indonesia develop an accountable and reliable tax audit system as implemented by tax authorities in the Netherlands. Tax audit optimisation can be done by increasing the database through digitalisation and data integration to facilitate information exchange. After implementing policy transformation, it is expected that taxpayer compliance and tax legitimacy will also increase